Dimensione medievale e finalità parenetiche nei cori dell’Ecerinis - Bosisio, Matteo (Incontri. Rivista europea di studi italiani, 2013)
Medieval Dimension and Parenetic Purposes of the Choruses of the Ecerinis Mussato’s Ecerinis, the first tragedy in European literature, consists of 629 verses; they recall the dramatic period between 1237 and 1259, when Ezzelino III da Romano ruled over Padua. The author’s instructions (Ep. I, 136) and the coeval comment by Guizzardo da Bologna and Castellano da Bassano prove that the work served to contemporaries as an example and warning against Cangrande della Scala. In fact, the lord of Verona is the real threat against whom the parenetical message of the text is addressed. Thus the article, analyzing the contingent features of the tragedy, situates the Ecerinis within the historical and cultural context of Padua between the thirteenth and fourteenth centuries and highlights the role of the choruses. If the first two choruses tend to put the viewer-reader in a dramatic atmosphere − which involves him emotionally, reminding him of his own negligence and also showing him the risks of a new tyranny – the third chorus infuses hope of redemption, provided that Padua’s citizens follow the former examples of courage and loyalty. Conversely, in the last two choruses the previous scenes of despair and resignation are reversed; however, a final victory, as the one achieved by Padua’s army fifty years before, will only be possible again through a fast reaction of the population.